Perencanaan Dan Normalisasi Drainase Ring Dalam Kereta Api Di Akademi Perkeretaapian Indonesia Madiun - Aghastya, Adya (Politeknik Perkeretaapian Indonesia Madiun, 2018)
Railway infrastructure is a railroad track, train station and train operation facilities so that trains can be operated. One component of the railway infrastructure is drainage. Railroad drainage is an infrastructure that functions to channel surface water to water bodies and / or artificial infiltration buildings. In the current field research the condition of the railroad drainage channel at the Indonesian Railroad Academy is not in the right conditions due to inundation and siltation which is mixed with the growth of wild plants caused by drainage structures that are not suitable for installation and not in accordance with the topography the area. From the facts in the field, a review of the problems in the drainage was conducted. The drainage flow pattern of the railroad should be flowed to the lake which is the final drainage channel, but this need has not been fully met. From the above problem an alternative is taken to solve the first problem namely Planning and Normalization of Drainage Channels includes (drainage cleaning, drainage elevation, construction of new drainage), the second solution is the construction of supporting buildings including the construction of culverts, construction of gates and construction of pump houses